2015
DOI: 10.1016/j.jvsc.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

An ex vivo approach to complex renal artery aneurysm repair

Abstract: Ex vivo repair technique for a complex renal artery aneurysm may have several advantages. Smaller incision size and use of minimally invasive techniques may decrease incisional morbidity and improve recovery time, especially in patients with a high body mass index. Improved visualization afforded by back-table methods may also be valuable when repair of aneurysms involving multiple branches is necessary. We report of a successful case of laparoscopic nephrectomy, followed by back-table aneurysmorrhaphy and aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Laparoscopic or robotic nephrectomy for ex vivo repair of RAAs has been described. 6 , 12 , 13 Gallagher et al 6 noted no incisional morbidity or ureteral complications, renal function remained unchanged, and arterial patency was comparable to that after open nephrectomy, with a mean hospital stay of 4 days in a series of 65 RAA repairs via laparoscopic nephrectomy and autotransplantation.…”
Section: Discussionmentioning
confidence: 98%
“…Laparoscopic or robotic nephrectomy for ex vivo repair of RAAs has been described. 6 , 12 , 13 Gallagher et al 6 noted no incisional morbidity or ureteral complications, renal function remained unchanged, and arterial patency was comparable to that after open nephrectomy, with a mean hospital stay of 4 days in a series of 65 RAA repairs via laparoscopic nephrectomy and autotransplantation.…”
Section: Discussionmentioning
confidence: 98%
“…In a case reported by Scherrer et al, an ex vivo aneurysmorrhaphy was performed after autotransplantation in an obese 66-year-old man, which offered the advantage of enhanced visualization over an in vivo multi-branch reconstruction using a saphenous vein graft. 14 English et al reported 36 RAA repairs performed ex vivo, with low morbidity and mortality, no unplanned nephrectomy, and high patency rates. 13 Given the young age of our patient, redundancy of the renal artery, anatomic location of right RAA and multi-lobular nature, we elected to proceed with open repair with primary reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular surgical techniques may be used in the case of an amenable morphology and with more proximal lesions; however, in cases where the RAAs are more distal and hilar, open surgical procedures are required. In these cases, an ex vivo repair for a complex RAA is a minimally invasive procedure that allows for a smaller incision and, therefore, improved recovery times and reduced incisional morbidity [5].…”
Section: Discussionmentioning
confidence: 99%
“…Through this procedure, postoperative tubular necrosis was avoided and when observing the period between six months to six years, 95% of the patients were reported to have been cured or improved [6]. Similarly, Scherrer et al, in continuation of a series of seven successful ex vivo repairs of RAAs in donor kidneys, reported another case of a 66-year-old man, who was hypertensive despite two maintenance medications [5]. The smaller incision through the laparoscopic method allowed for an improved recovery time as well as fewer complications.…”
Section: Discussionmentioning
confidence: 99%